2013
DOI: 10.1002/bies.201300096
|View full text |Cite
|
Sign up to set email alerts
|

Networks of lexical borrowing and lateral gene transfer in language and genome evolution

Abstract: Like biological species, languages change over time. As noted by Darwin, there are many parallels between language evolution and biological evolution. Insights into these parallels have also undergone change in the past 150 years. Just like genes, words change over time, and language evolution can be likened to genome evolution accordingly, but what kind of evolution? There are fundamental differences between eukaryotic and prokaryotic evolution. In the former, natural variation entails the gradual accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…In List et al (2014a), this was done by testing to which degree known borrowings in an Indo-European dataset were readily identified by the method. In this study, the mln approach identified 72% of all known borrowings correctly.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…In List et al (2014a), this was done by testing to which degree known borrowings in an Indo-European dataset were readily identified by the method. In this study, the mln approach identified 72% of all known borrowings correctly.…”
Section: 3mentioning
confidence: 99%
“…In a pilot study by Nelson-Sathi et al (2011), the mln approach was used to assess borrowing frequencies during Indo-European language history. In List et al (2014a), an improved version of this approach was presented and successfully applied to a small set of 40 Indo-European languages, where it identified 72% of all known borrowings in the data. In List et al (2014b), the method was applied to Chinese dialect data, where it revealed a much higher amount of characters suggestive of borrowing than was inferred for Indo-European (48-55% in Chinese vs. 31% in Indo-European).…”
mentioning
confidence: 99%
“…It is important to note that the MLN approach is an automatic approach based on tree topology and the 42 suggestive cases of borrowing recovered by MLN, which include 33 English loanwords identified by Donohue et al [22], cannot be considered as crystal-clear borrowings. They may comprise some false positives, which can be due to parallel semantic development [21], for example.…”
Section: Methodsmentioning
confidence: 99%
“…While the use of this list may lead to a certain decrease in the number of loanwords [20], it remains helpful for detecting the most important word borrowing trends [21]. For example, the traditional 200-meaning English Swadesh list includes 33 confirmed loanwords (16.5 %) [22] and 10 additional “irregular phylogenetic patterns” which might be suggestive of unrecognized borrowings [21]. Moreover, in a recent revision of the Albanian Swadesh list 31.8 % of its entries were identified as probable borrowings [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation